Black Magic and Respecting Persons -- Some Perplexities - Smilansky Saul; Räikkä Juha (Wiley, 2022)
Black magic (henceforth BM) is acting in an attempt to harm human beings through supernatural means. Examples include the employment of spells, the use of special curses, the burning of objects related to the purported victim, and the use of pins with voodoo dolls. For the sake of simplicity, we shall focus on attempts to kill through BM. The moral attitude towards BM has not been, as far as we know, significantly discussed in contemporary analytic philosophy. Yet the topic brings up interesting questions and poses challenges, occasionally even reaching the level of paradoxes. Ideas of respecting persons, in particular, will be seen to be challenged by this form of magic. The notion of respecting persons will be treated here broadly and pluralistically. Indeed part of the interest in the discussion will be the unfolding of the diverse ways in which this term should be understood, and the contrasts between its various uses. Often, as we shall see, respect for persons and disrespect for them, in different senses, will co-exist, and the dilemma will be one where avoiding some forms of disrespect will involve us in disrespect in other senses.